Vos désirs sont des échos ou des égos? et Sexualités et handicaps : les terres promises d’un bonheur conforme dans Nos existences handies - Blanquer, Zig; Dufour, Pierre (Nos existences handies, 2022)
Nos existences handies” est un recueil de textes de Zig Blanquer. Ces essais puissamment politiques et enthousiasmants abordent le validisme, l’autonomie des handis, la sexualité, critiquent la notion de courage et de charité… Ils ont été écrits sur une vingtaine d’années, parus dans des revues et médias en ligne et hors ligne.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; capacitisme; corps; cours; discipline; europe; france; inégalités; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexualité; soc3113; sociologie; systèmes d'oppressions; thématiques

Sexual citizenship through resistance: a movement that centers disabled women’s voices - MacKeigan, Tanya (Disability & Society, 2021)
This research examines the discourses that shape disabled women’s sexual subjectivity. I wanted to see how disabled women’s understanding of themselves as sexual is socially influenced. I held a focus group and individually interviewed five self-identified physically disabled women about their sexual lives. They shared detailed stories of personal experiences and societal influences. The main social influences that were present in the women’s stories were ableism, sexism, and resistance; the focus of this article is resistance. Resistance discourses challenge mainstream notions of disability and sexuality and combat the oppression that ableism and sexism can create. It is important work to highlight these resistance narratives; they are often overlooked in society. Diverse social understandings of disability and sexuality are needed, and it is important that they come from disabled people. This research seeks to make space for disabled perspectives in the interest of sexual inclusivity and sexual citizenship for disabled women.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; EDI; accessibilité; amériques; approches et analyses; canada; capacitisme; care; colombie-britannique; corps; cours; discipline; droit des personnes en situation de handicap; intersectionnalité; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex1911; sex1920; sexisme; sexualité; systèmes d'oppressions; thématiques; travail social; études critiques du handicap

The Routledge handbook of disability and sexuality - Shuttleworth, Russell; Mona, Linda (Routledge international handbooks, 2021)
This handbook provides a much-needed holistic overview of disability and sexuality research andscholarship. With authors from a wide range of disciplines and representing a diversity of nationalities, it provides a multi-perspectival view that fully captures the diversity of issues and outlooks. Organised into six parts, the contributors explore long-standing issues such as the psychological, interpersonal, social, political and cultural barriers to sexual access that idsabled people face and their struggle for sexual rights and participation. The volume also engages issues that have been on the periphery of the discourse, such as sexual accomodations and support aimed at facilitating disabled people's sexual well-being; the socio-sexual tensions confronting disabled people with intersecting stigmatised identities such as LGBTBI or asexual; and the sexual concerns of disabled people in the Global South. It interrogates disability and sexuality from diverse perspectives, from more traditional psychological and sociological models, to various subversive and post-theoretical perspectives and queer theory. This handbook examines the cutting-edge, and sometimes ethically contentious, concerns that have been repressed in the field. With current, international and comprehensive content, this book is essential reading for students, academics and researchers in the areas of disability, gender and sexuality, as well as applied disciplines such as healthcare pratictionners, counsellors, psychology trainees and social workers.
Keywords: EDI; LGBTQIA2+; accessibilité; approches et analyses; capacitisme; care; corps; cours; discipline; histoire et politique; identités LGBTQIA2+; intersectionnalité; outils; ouvrages de références; premier cycle; ressource en ligne; santé; sciences de la santé; sciences humaines; sex1911; sex1920; sexologie; sexualité; systèmes d'oppressions; thématiques; travail social; études critiques du handicap

Les droits sexuels des personnes handicapées: réflexion sur le développement du droit international - Mona Paré (Genre, Sexualité et Société, 2018)
Interest in the sexuality of persons with disabilities is growing and research improves our understanding of issues in this regard. This leads us to a reflection on the definition of sexual rights in international law, and the way in which sexual rights of persons with disabilities are understood. Examining existing norms leads to the conclusion that despite developments in this area, sexual rights remain largely limited to the field of health, and this has not changed with the adoption of the Convention on the Rights of Persons with Disabilities (CRPD). The limited claims related to these rights during the negotiations of the CRPD is surprising given the significant participation of persons with disabilities. Yet, despite the lack of clarification in relation to the sexual rights of persons with disabilities in the convention, the practice of interpretation of law remains a way to develop international law in this field, particularly through the evolving concept of non-discrimination.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; EDI; approches et analyses; capacitisme; cours; discipline; droit; droit des personnes en situation de handicap; droit international; histoire et politique; militance; premier cycle; périodes historiques; ressource en ligne; santé; science politique et droit; sex1920; sexualité; systèmes d'oppressions; thématiques; études critiques du handicap

(Re)penser l’accès aux espaces intimes en contexte de handicap intellectuel: une question de droit et de participation sociale - Pariseau-Legault, Pierre; Holmes, Dave (Revue générale de droit, 2017)
En contexte de handicap, la question de l’accès est constituée généralement de l’éventail des aménagements individuels et collectifs nécessaires afin de faciliter l’occupation d’espaces publics. A contrario, peu de choses sont dites à propos des aménagements possibles et potentiels requis afin de sécuriser l’espace privé des personnes identifiées comme ayant un handicap intellectuel. Ce sont pourtant ces lieux intimes, au sein desquels se développent et se déploient l’identité et l’expression affectives, qui sont susceptibles de contribuer à une reconnaissance plus soutenue de l’identité affective et de la citoyenneté sexuelle de ces personnes. Inspirée par les théories d’Erving Goffman et de Michel Foucault, une analyse phénoménologique interprétative (API) fut réalisée auprès des personnes ayant un handicap intellectuel et de leurs proches aidants afin d’explorer cette situation. Nos constats préliminaires suggèrent l’existence d’un processus de négociation complexe des acteurs, des lieux et des moments nécessaires afin de favoriser le développement de la vie affective et sexuelle. De ce fait, trois modes d’existence semblent cohabiter au sein d’une matrice complexe : la dépossession, l’habitation et l’occupation des espaces de socialisation et d’expression affective. Il est proposé d’aborder cette problématique en tant que dynamique géopolitique intégrant les processus d’exclusion des pratiques sexuelles des espaces privés, leur projection dans des espaces publics et, finalement, la juxtaposition de ces deux sphères, publique et privée dans des espaces mixtes. Nous discuterons enfin des implications de cette réflexion sur la « question de l’accès » et sur les politiques publiques visant à diminuer la discrimination systémique ciblant les personnes identifiées comme ayant un handicap intellectuel.
Keywords: approches et analyses; capacitisme; care; corps; cours; discipline; droit; histoire et politique; inégalités; justice sociale; premier cycle; ressource en ligne; santé; science politique et droit; science politique et droit de la santé; sciences; sciences de la santé; sciences politiques; sex1920; sexualité; systèmes d'oppressions; thématiques

Reproductive and Sexual Health of People with Physical Disabilities: A Metasynthesis - Nguyen, Thi Tu An; Liamputtong, Pranee; Monfries, Melissa (Sexuality and Disability : A Journal Devoted to the Psychological and Medical Aspects of Sexuality in Rehabilitation and Community Settings, 2016)
This article provides an overview on reproductive and sexual health of people with physical disabilities in developed and underdeveloped countries from 1995 to 2011. Based on the metasynthesis approach, the authors reviewed 15 qualitative studies. These studies were searched using Medline, CINAHL, CINAHL (health), ProQuest Central, Google Scholar, Cochrane, Embase, Informit Health, Sciences Direct, Pubmed, Pubmed Health, AAHD (abstracts), ProQuest Journal (sexuality and disability) and were also manually searched. All studies were judged on their qualities using the Critical Appraisal Skills Programme. Reproductive health, sexual attractiveness and experiences, reproductive and sexual health knowledge, and dealing with reproductive and sexual health issues were four main themes that emerged from these studies. This paper proposes a new model to explain the factors that impacted the reproductive and sexual life of people with physical disabilities: internal and external factors. Implications for health and social care are discussed in light of the findings.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; capacitisme; care; cours; discipline; justice reproductive; médecine; métasynthèse; premier cycle; psychologie; périodes historiques; ressource en ligne; santé; sciences; sciences humaines; sex1920; sexualité; systèmes d'oppressions; thématiques; travail social

Des hommes aux prises avec l’agencement valido-viril dans L'expérience handie : handicap et virilité - Dufour, Pierre; Welzer-Lang, Daniel (L'expérience handie : handicap et virilité, 2013)
Parler de handicap, investir le champ du handicap conduit à questionner les manières de porter le geste, d'agir, de se mouvoir, que chacun d'entre nous a coutume de tenir pour neutres et ordinaires. Car comment construit-on sa virilité quand le corps ne correspond pas au standard, quand la force ou le muscle fait défaut ? Comment parle-t-on de soi, lorsqu'on est en situation de handicap ? Comment appréhende-t-on son expérience, lorsque certains gestes ne peuvent se faire en autonomie, et nécessitent une coréalisation, l'aide, la coopération de l'autre ? A travers des entretiens non directifs d'hommes "handis", comme ils se définissent eux-mêmes, complétés par de l'observation participante, Pierre Dufour, lui-même en fauteuil, dénoue le discours qui sous-tend la situation de handicap, le regard que l'on porte sur soi, sur sa virilité, sur sa capacité à s'affranchir des standards et d'un vocabulaire issus d'un agencement du monde "valido-viril" qui ne sont d'aucune utilité pour décrire son quotidien : parle-t-on d'un corps qui rampe sur la plage pour aller se baigner ? Qui fait la "brouette" pour monter un escalier ? Quelle place ambiguë le sport "handi" tient-il vraiment dans ce rapport au corps ? On questionne rarement les normes et les valeurs issues des modalités d'être valides. Or comment soutenir que disposer d'un corps muni de bras et de jambes, mobiles, allant par deux, n'induirait aucune norme, n'orienterait en rien les descriptions ? Croisant les thèmes du handicap et du genre, l'auteur interroge à la fois les pratiques d'hommes se déplaçant en fauteuil roulant et le stock social des discours possibles sur la diversité corporelle. Par son approche originale, cet ouvrage apporte un éclairage peu courant, et notamment sur le thème de l'assistance sexuelle.
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; capacitisme; corps; cours; discipline; europe; france; inégalités; premier cycle; privilèges; périodes historiques; régions géographiques; sciences humaines; sexualité; soc3113; sociologie; systèmes d'oppressions; thématiques

Rénover la pratique de l’éducation à la sexualité des personnes ayant des incapacités intellectuelles - Dupras, André (Nouvelles pratiques sociales, 2013)
La reconnaissance du droit des personnes ayant des incapacités intellectuelles à une éducation à la sexualité a généré la conception et l’implantation de programmes éducatifs. À quelles valeurs et croyances les professionnels se réfèrent-ils pour organiser l’éducation à la sexualité? Une analyse critique des approches dominantes actuelles est proposée pour contribuer à leur progrès et à leur transformation. Pour dépasser les limites des approches paternalistes et objectivistes, il est suggéré d’adopter un nouveau paradigme fondé sur des perspectives participatives et subjectivistes. Le renouvellement de l’éducation à la sexualité pourrait procéder par énovation en enrichissant et en élargissant les pratiques existantes.
Keywords: amérique du nord; amériques; approches et analyses; canada; capacitisme; discipline; intervention sociale; québec; ressource en ligne; régions géographiques; sciences humaines; sexologie; sexualité; systèmes d'oppressions; thématiques; éducation sexuelle

Sex and disability - McRuer, Robert; Mollow, Anna (Duke University Press, 2012)
The title of this collection of essays, Sex and Disability, unites two terms that the popular imagination often regards as incongruous. The major texts in sexuality studies, including queer theory, rarely mention disability, and foundational texts in disability studies do not discuss sex in much detail. What if'sex'and'disability'were understood as intimately related concepts? And what if disabled people were seen as both subjects and objects of a range of erotic desires and practices? These are among the questions that this collection's contributors engage. From multiple perspectives—including literary analysis, ethnography, and autobiography—they consider how sex and disability come together and how disabled people negotiate sex and sexual identities in ableist and heteronormative culture. Queering disability studies, while also expanding the purview of queer and sexuality studies, these essays shake up notions about who and what is sexy and sexualizable, what counts as sex, and what desire is. At the same time, they challenge conceptions of disability in the dominant culture, queer studies, and disability studies.Contributors. Chris Bell, Michael Davidson, Lennard J. Davis, Michel Desjardins, Lezlie Frye, Rachael Groner, Kristen Harmon, Michelle Jarman, Alison Kafer, Riva Lehrer, Nicole Markotić, Robert McRuer, Anna Mollow, Rachel O'Connell, Russell Shuttleworth, David Serlin, Tobin Siebers, Abby L. Wilkerson
Keywords: approches et analyses; arts; autobiographie; capacitisme; cours; discipline; ethnographie; premier cycle; queer; ressource en ligne; sciences humaines; sex1920; sexualité; systèmes d'oppressions; thématiques; études critiques du handicap; études littéraires

Intimate Justice: A Critical Analysis of Sexual Satisfaction - McClelland, Sara I. (Social and Personality Psychology Compass, 2010)
This article elaborates an intimate justice framework to help guide research on sexual satisfaction. Using a critical historiography approach, I examine the etiology and development of the psychological construct of “satisfaction” over the last century and argue that social and political antecedents to satisfaction ratings are an essential and under-theorized aspect of research in this field. By examining what are considered to be the most influential definitions in life satisfaction research, I identify conceptual gaps, oversights, and disagreements that characterize this body of work, and specifically its theoretical treatment of inequity. Moving to the intimate domain, I argue that the field of sexual satisfaction must include theories and methods that systematically consider the role of social and sexual stigmas as antecedents to sexual satisfaction ratings. In the conclusion, building from existing social justice theories, I propose an intimate justice framework as a means to guide research that can highlight issues of entitlement and deservingness in sexual satisfaction research. This is particularly important as sexual satisfaction is increasingly used as an indicator of individual and relational well-being; however, this construct is presently limited and inadequately measured for women and men who experience limited sexual rights in the socio-political domain because of their gender and/or sexual minority status.
Keywords: approches et analyses; capacitisme; cours; discipline; intersectionnalité; justice sociale; premier cycle; psychologie; racisme; ressource en ligne; sciences humaines; sex1920; sexisme; sexualité; systèmes d'oppressions; thématiques

Pushing the limits disabled dykes produce culture - Tremain, Shelley (Women's Press, 2009)
Cet impressionnant recueil de prose, de poésie, de chansons et d'art visuel rédigé par des lesbiennes handicapées est la première de deux anthologies liées (la seconde est un recueil d'essais). Dans son introduction percutante (« Nous sommes ici. Nous sommes handicapés et queer. Habituez-vous-y »), la rédactrice en chef Shelley Tremain appelle à la reconnaissance et à la compréhension du monde selon les lesbiennes handicapées. La collection elle-même est colérique, compatissante, drôle et surtout émouvante. Sherree Clark présente des extraits de son recueil de poésie et d'art Living with Arthritis. Margot K. Lane célèbre la sexualité dans un merveilleux poème intitulé « Full day ». Le récit posthume de Kathleen Martindale sur le cancer du sein est un appel à l’action contre le personnel médical insensible, tout comme la chronique de Kathleen Rockhill sur sa guérison d’un accident de voiture dévastateur. Combinant colère et célébration, Pushing the Limits est une révélation.
Keywords: amériques; anthologie; approches et analyses; arts; canada; capacitisme; corps; lesbianisme; littérature; outils; ouvrages de références; patriarcat; personnes lesbiennes; poésie; queer; racisme; ressource en ligne; régions géographiques; santé; sexisme; sexualité; systèmes d'oppressions; thématiques; états-unis

Contested pleasures: The sociopolitical economy of disability and sexuality - Shildrick, Margrit (Sexuality Research & Social Policy, 2007)
Consideration of sexual pleasure in the lives of people with disabilities plays little part in lay consciousness, and practically none in social policy. This article investigates such repression by engaging with a cultural imaginary that fears nonnormative sexuality as being a potential point of societal breakdown. Recent work in disability studies gives a very different understanding of the sexuate body that opens up the parameters of sexuality for everyone. This work challenges current social policy’s supposedly rational utilitarian basis and the principle of equality that together ground a sociopolitical economy of disability predicated on rehabilitation or compensation. Nonetheless, the call for sexual citizenship for people with disabi lities is fraught with difficulties, not least regarding the potential extension of govern mentality. An effective approach not only will take into account the sociopolitical aspects of this issue but also will respond to both the full embodiment of disability and its significance in mainstream culture.
Keywords: EDI; accessibilité; approches et analyses; arts; bioéthique; capacitisme; corps; cours; discipline; intersectionnalité; justice sociale; philosophie; premier cycle; ressource en ligne; sciences; sciences humaines; sex1911; sex1920; sexualité; systèmes d'oppressions; thématiques; études critiques du handicap; études littéraires